Sharpened chronic apical periodontitis treatment with pasta 3 Mix-MP - Hinostroza del Pino, Maycol (2015)
The purpose of this case is to show the use of intracanal medication Oshino paste (3Mix-MP). A patient who had a pulp necrosis with chronic apical periodontitis in the piece 42, underwent endodontic treatment in 2013, but in 2014 returns with a more severe apical lesion and the diagnosis of apical periodontitis, extra oral fistula; the patient did not want to lose the tooth so that the possibility of nonsurgical treatment of second intention using paste 3 MIX-MP as intracanal medication was evaluated. Controls for 3 months with intracanal medication were performed, the clinical disappearance of fistula was observed and periapical lesion decrease, improving the prognosis. So we proceed to seal the tooth and evaluated for 12 months, coming to observe bone repair, then the prosthetic restoration of the piece was done.